2009
DOI: 10.1093/heapro/dap031
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to regular exercise among adults at high risk or diagnosed with type 2 diabetes: a systematic review

Abstract: The aim of this systematic review was to identify the reported barriers to regular exercise among adults either at high risk or already diagnosed with type 2 diabetes (T2D), because of the importance of exercise in the prevention of T2D. We searched the MEDLINE, Cinahl and PsycINFO databases. All potentially relevant articles were reviewed by two researchers, and 67 titles were found, of which 13 papers met inclusion criteria. Internal and external barriers to exercise were identified among adults either at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
191
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(208 citation statements)
references
References 53 publications
10
191
0
7
Order By: Relevance
“…The reasons for the unhealthy trajectories may be multifold: work, school and life strain can cause unhealthy coping behaviors, hamper possibilities or vitality to exercise, and increase proneness to use alcohol regularly and excessively [19][20][43][44][45]. These may partially explain the trajectory of deteriorated health behaviors.…”
Section: Students) When Compared To All the Unemployed Seeking Work mentioning
confidence: 99%
“…The reasons for the unhealthy trajectories may be multifold: work, school and life strain can cause unhealthy coping behaviors, hamper possibilities or vitality to exercise, and increase proneness to use alcohol regularly and excessively [19][20][43][44][45]. These may partially explain the trajectory of deteriorated health behaviors.…”
Section: Students) When Compared To All the Unemployed Seeking Work mentioning
confidence: 99%
“…Previous research on physical activity interventions has collectively found that health professionals often lack confidence, experience and ongoing feedback to promote the use of physical activity [47][48][49]. The authors of the RE-AIM framework suggest that the provision of training and support for individuals delivering interventions may improve protocol fidelity via an atmosphere of collaboration and peer problem solving [20].…”
Section: Adoptionmentioning
confidence: 99%
“…Recommendations for levels of physical activity place heavy emphasis on performing moderate and/or vigorous-intensity cardiorespiratory exercise training (Garber et al 2011), which is associated with a substantial timecommitment. 'Lack of time' is often cited as a barrier to being physically active (Korkiakangas et al 2009;Reichert et al 2007), suggesting that these guidelines may not be the ideal approach to increase physical activity levels to improve public health.…”
Section: Introductionmentioning
confidence: 99%